Guideline on sampling and analysis of forest soils for GHG reporting - Vera Makowski; Steffi Dunger; Nicole Wellbrock (Johann Heinrich von Thünen-Institut, 2023)
As part of international agreements, countries must report their greenhouse gas emissions. In associations of states such as the EU, it is desirable that the data used for reporting is also comparable. To date, there have been various methods for collecting data on forest soil, some of which differ so greatly from one another due to historically evolved circumstances that the data obtained cannot be harmonized. In addition, there are countries that have not yet collected any data, as a systematic survey, whether as part of an inventory or long-term monitoring, is time-consuming and cost-intensive. With this guideline, we therefore propose a basis that can be used in future to collect data for greenhouse gas (GHG) reporting in forest soils. The methodology is based on the ICP Forests manual and is limited to the parameters relevant for GHG reporting and their interpretation. It is possible to add individual parameters. With the help of the guideline, forest soil investigations can be linked to existing inventories (e.g. forest inventories) or the existing ICP Forests network can be consolidated with less complex sites. – – Im Zuge von internationalen Abkommen müssen Länder ihre Treibhausgase berichten. In Staatenverbünden wie der EU ist hierbei wünschenswert, dass die Daten, die zur Berichterstattung herangezogen werden, auch vergleichbar sind. Für die Datenerhebung im Waldboden gibt es bisher verschiedene Methoden zur Datenerhebung, die sich durch historisch gewachsene Gegebenheiten teilweise so stark voneinander unterscheiden, dass die gewonnenen Daten nicht harmonisierbar sind. Hinzu kommen Länder, die bisher noch keine Daten erheben, da eine systematische Erhebung, sei es im Zuge einer Inventur oder eines langfristigen Monitorings, zeit- und kostenintensiv ist. Daher schlagen wir mit dieser Guideline eine Grundlage vor, mit der in Zukunft für die Treibhausgasberichterstattung (THG) im Waldboden Daten erhoben werden können. Die Methodik basiert auf dem Manual des ICP Forests und ist auf die für die THG und ihre Interpretation relevanten Parameter beschränkt. Eine Erweiterung um einzelne Parameter ist möglich. Mit Hilfe der Guideline können Waldbodenuntersuchungen an bestehende Inventuren (z. B. Waldinventuren) angegliedert werden oder das bestehende ICP Forests Netzwerk mit weniger aufwendigen Standorten verdichtet werden.
urn:nbn:de:gbv:253-202311-dn067225-6
Keywords: 630; Forest soil; inventory; monitoring; greenhouse gas reporting; Waldboden; Inventur; Monitoring; Treibhausgasberichterstattung